Chhaupadi Culture and Reproductive Health of Women in Nepal. (October 2015) - Ranabhat, Chhabi; Kim, Chun-Bae; Choi, Eun Hee; Aryal, Anu; Park, Myung Bae; Doh, Young Ah
Different sociocultural barriers concerning women's health are still prevalent. Chhaupadi culture in Nepal is that threat wherein menstruating women have to live outside of the home in a shed-like dwelling. Our study aims to determine the factors of reproductive health problems related to Chhaupadi. A cross-sectional study was performed with women of menstrual age (N = 672) in Kailali and Bardiya districts of Nepal. Data were collected with stratified sampling and analyzed using SPSS. Reproductive health problems were observed according to the World Health Organization reproductive health protocol. Regression analysis was performed to show the association between relevant variables. Results reveal that one fifth (21%) of households used Chhaupadi. Condition of livelihood, water facility, and access during menstruation and precisely the Chhaupadi stay was associated ( P < .001) with the reproductive health problems of women. The study concludes that Chhaupadi is a major threat for women's health. Further research on appropriate strategies against Chhaupadi and menstrual hygiene should be undertaken.